2010
DOI: 10.1002/adem.201000251
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Functionally Graded Carbon Nanotube‐Reinforced Aluminum Matrix Composite

Abstract: Functionally graded materials (FGMs) are compositionally gradient materials which were first proposed in Japan in 1984. [1] They have been suggested as a way of fabricating bulk materials with tailored properties because they can achieve the controlled distribution of the desired characteristics within the same bulk material. This FGM can be applied for engineering parts instead of coated materials. However, careful selection of the component materials, particularly the reinforcement, is required to reliably a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(55 citation statements)
references
References 19 publications
0
55
0
Order By: Relevance
“…To avoid abrupt change of the material properties in the functionally graded CNTRCs, a linear variation of the volume fraction of CNTs in the thickness direction is assumed and can readily be achieved in practice [9]. As the same in [35], three types of FG-CNTRCs, i.e.…”
Section: Theoretical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid abrupt change of the material properties in the functionally graded CNTRCs, a linear variation of the volume fraction of CNTs in the thickness direction is assumed and can readily be achieved in practice [9]. As the same in [35], three types of FG-CNTRCs, i.e.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…He used a linear distribution pattern of CNTs along the thickness direction of the plates and found that the functionally graded CNT reinforcements can significantly change the bending behavior of the CNTRC plates. The concept of functionally graded nanocomposites has been realized in a recent experimental study [9] where a functionally graded CNT reinforced aluminum composite was fabricated using a powder metallurgy route. These pioneer works have stimulated extensive studies on the bending, buckling and vibration responses of CNTRC structures in recent years [10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Another frequent manufacturing process of FG nanocomposites uses assembling of different layers of materials. For example, aluminium -CNT composite is produced from layers containing different fractions of CNT [17]. In this particular case, Vickers hardness of each particular layer was measured with results varying by a factor of 7.…”
Section: Introductionmentioning
confidence: 99%
“…7 Numerical results of Shen reveal that nonlinear bending behavior can be considerably improved using an FG distribution of CNTs in the matrix. Recently, Kwon et al 8 have successfully achieved the linear distribution of CNTs in a matrix, rather than the uniform distribution of CNTs in a matrix using the power metallurgy fabrication process, which proves the feasibility of FG-CNTRC.…”
Section: Introductionmentioning
confidence: 98%